Analysis and assessment of using an integrated solar energy based system in crude oil refinery - Altayib, Khalid; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Crude oil heating is a significant and energy intensive process in crude oil production. Large amounts of heat are required to preheat crude before it processed in a crude distillation unit. This study aims to investigate a novel thermal design for an industrial heating process, study an integrated system of different components into overall plant, incorporate solar energy in heating application and assess the key performance indicators of a crude oil refinery employing three preheating stages. Around 10% percent of the required preheating is attained through solar energy instead of conventional gas-burning techniques during the crude oil heating process. To address the intermittent behavior of the sun, a thermal storage system (TES) is incorporated. The solar energy based integrated system is also used to produce electricity through an integrated Rankine cycle. Some assessments of possible improvements are suggested by the thermodynamic analysis. The performance assessment indicates that the overall energetic and exergetic efficiencies are 60.94% and 19.34%, respectively. This study also reveals that the largest exergy destruction rate occurs in the solar field system, TES and the heat exchangers.
Keywords: Solar energy; Crude oil; Heating; Energy; Exergy; Efficiency; PERFORMANCE ASSESSMENT; MULTIGENERATION SYSTEM; EXERGY ANALYSIS; FUEL-CELL; COLLECTORS; HYDROGEN; STEAM; Thermodynamics; Energy & Fuels; Engineering; Mechanics